On-Line Photo-Assisted Catalytic Degradation of Carbofuran - Lamiri, A.; Morales-Rubio, A.; De la Guardia, M. (Ciencia)
An on-line photo-assisted catalyzed degradation procedure has been developed for the detoxification of waters polluted with carbofuran. The system involves the use of an UV lamp and a TiO2 slurry, employed as photocatalyst, for the on-line water treatment. Different experimental variables, such as pesticide and catalyst concentrations, irradiation time and pH, were evaluated by studying their effect on the degradation of carbofuran. Under the best photodegradation conditions, 15 mg L-1 carbofuran can be totally mineralized in less than 2.5 minutes in the presence of 0.4 mg mL-1 TiO2